Thermodynamics and dielectric properties of the NH₄H₂PO₄ type antiferroelectrics - Levitskii, R.R.; Lisnii, B.M.; Baran, O.R. (Condensed Matter Physics, 2002)
Within the framework of the proton model we study thermodynamic and static dielectric properties of the ADP type antiferroelectrics with taking into account the tunnelling effects of protons on hydrogen bonds. In the fourparticle cluster approximation for the short-range interactions and in the mean field approximation for the long-range interactions we calculate the free energy, entropy, and components of static dielectric susceptibility of the crystals. We also get the system of equations for the sublattice proton order parameter and an equation for the phase transition temperature. We find the values of the theory parameters for the NH₄H₂PO₄ and NH₄H₂AsO₄ crystals and get a good agreement between the theoretical results and the corresponding experimental data for the temperature dependences of the spontaneous sublattice polarization, proton specific heat, longitudinal and transverse static dielectric permittivities of the crystals.